2007
DOI: 10.1021/nl0624723
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Distribution of TiO2−DNA Oligonucleotide Nanoconjugates Directed to Nucleolus and Mitochondria Indicates Sequence Specificity

Abstract: Deoxy DNA oligonucleotides hybridize to matching DNA sequences in cells, as established in the literature, depending on active transcription of the target sequence and local molarity of the oligonucleotide. We investigated the intracellular distribution of nanoconjugates composed of deoxy DNA oligonucleotides attached to TiO 2 nanoparticles, thus creating a locally increased concentration of the oligonucleotide. Two types of nanoconjugates, with oligonucleotides matching mitochondrial or nucleolar DNA, were sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(150 citation statements)
references
References 27 publications
4
146
0
Order By: Relevance
“…Microprobe SRXRF has proven itself as a technique for providing unequalled information regarding the distribution of metal and metalloid-containing drugs in cells and tumours at subtoxic and therapeutic doses. [8,26,[31][32]38,[40][41]56] Targets such as the nucleus, [26,38] including the euchromatin [32] and heterochromatin [8] regions, nucleoli, [32,48,52] membranes, and mitochondria [52] can be identified as sites of localisation following studies of existing and potential therapeutic and diagnostic agents. The technique has been invaluable for confirming theories of drug actions (namely, the coordinative action of cisplatin and its analogues) [38][39] and for confirming concepts associated with the modes of action of designed therapeutics (namely, confirmation of drug penetration to the site of dense DNA).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Microprobe SRXRF has proven itself as a technique for providing unequalled information regarding the distribution of metal and metalloid-containing drugs in cells and tumours at subtoxic and therapeutic doses. [8,26,[31][32]38,[40][41]56] Targets such as the nucleus, [26,38] including the euchromatin [32] and heterochromatin [8] regions, nucleoli, [32,48,52] membranes, and mitochondria [52] can be identified as sites of localisation following studies of existing and potential therapeutic and diagnostic agents. The technique has been invaluable for confirming theories of drug actions (namely, the coordinative action of cisplatin and its analogues) [38][39] and for confirming concepts associated with the modes of action of designed therapeutics (namely, confirmation of drug penetration to the site of dense DNA).…”
Section: Discussionmentioning
confidence: 99%
“…[35,[52][53] Consequently, it is not surprising that microprobe SRXRF is becoming recognised as a technique for imaging intracellular nanoparticles in efforts to develop and confirm the capabilities of these agents. [35,52] An exciting study has been reported by Paunesku et al [52] whereby they aimed to produce DNA-targeting TiO 2 nanoparticles that could be excited, causing the electropositive holes of the semiconductor to be injected into the DNA, ultimately leading to DNA scission. The important role of microprobe SRXRF was to establish whether these nanoparticles could be taken up by the cells and retained at their target DNA sequence.…”
Section: Nanoparticles and Nanoconjugatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the main interest of TiO 2 as a substitutive and repairing material, this material offers interesting surface characteristics [2,3] suitable to improve commonly used biomedical applications in e.g. immunology, oncology and molecular biology [4][5][6]. Previous studies have focused on different aspects of the sintering process, phase, composition, micro-and nanostructure of TiO 2 for specific application as a biomaterial.…”
Section: Introductionmentioning
confidence: 99%